2019
DOI: 10.1080/13696998.2019.1611587
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of percutaneous closure of a patent foramen ovale compared with medical management in patients with a cryptogenic stroke: from the US payer perspective

Abstract: Aims: To evaluate the cost-effectiveness of percutaneous patent foramen ovale (PFO) closure, from a US payer perspective. Lower rates of recurrent ischemic stroke have been documented following percutaneous PFO closure in properly selected patients. Stroke in patients aged <60 years is particularly interesting because this population is typically at peak economic productivity and vulnerable to prolonged disability. Materials and methods: A Markov model comprising six health states (Stable after index stroke, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…The analysis revealed that PFO closure is cost-effective in the base case model, resulting in an ICER of ¥3,318,152 per QALY gained. Previous costeffectiveness analyses outside Japan also revealed that PFO closure is cost-effective compared with medical therapy for cryptogenic stroke patients (11)(12)(13)(14)(15)(16). A cost-effectiveness study in the U.S. (11) showed that PFO closure achieved an ICER of $21,049 at five years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis revealed that PFO closure is cost-effective in the base case model, resulting in an ICER of ¥3,318,152 per QALY gained. Previous costeffectiveness analyses outside Japan also revealed that PFO closure is cost-effective compared with medical therapy for cryptogenic stroke patients (11)(12)(13)(14)(15)(16). A cost-effectiveness study in the U.S. (11) showed that PFO closure achieved an ICER of $21,049 at five years.…”
Section: Discussionmentioning
confidence: 99%
“…Some cost-effectiveness analyses outside Japan have compared PFO closure and medical therapy alone for cryptogenic stroke patients and have shown that PFO closure is cost-effective for quality-adjusted life years (QALYs) gained. (11)(12)(13)(14)(15)(16). However, there have been no cost-effectiveness analyses in Japan and such analyses, which include cost information, utility scores, and a lifetable would be more convincing than cost-effectiveness analyses done outside Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that embolism caused by PFO is related to the size and shunt volume of PFO [29,30] . The larger the diameter of PFO, the greater the shunt volume, and the higher the probability of cerebral embolism [31] .…”
Section: Discussionmentioning
confidence: 99%
“…In diesem Kontext erscheint auch eine Abwägung des Nettonutzens für den Patienten relevant: seltene, im Einzelfall aber schwere periprozedurale Komplikationen vs. Risikoreduktion von ischämischen Schlaganfällen mit regelhaft offenbar weniger schweren neurologischen Defiziten [3,9]. Dieser Aspekt sollte auch in Kosten-Nutzen-Analysen [25]…”
Section: Merkeunclassified